PEDAGOGICAL ACTIVITY OF ATANIYOZ KHOJANIYOZ UGLI NIYOZIY (Scientific journal of the Fergana State University, 2024)
In this article there is information on the life and activities of Otaniyoz Khojaniyoz ugli Niyazi, his scientific heritage, his education in the madrasas of Khiva and Bukhara, the fact that he was a teacher in the Madrasas of Abdullah Khan and Muhammad Rahim Khan II in Khiva, he taught students, organized the study process based on a new system, solved various problems in the madrasa, also there is information that he was also interested in mathematics.